Wartość edukacji w życiu seniora - Malik, Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2022)
Due to changes in contemporary societies, interest in researching the life of senior citizens has increased. Today, senior citizens benefit from a wide educational offer, which include universities of the third age, senior citizens’ clubs, national and local programmes and activities at cultural and educational institutions. The aim of this article is to characterise the activities of senior citizens by discussing examples of selected educational offers developed to empower senior autonomy and self-responsibility as well as their social and intercultural engagement. The literature on the subject and the author’s own experience in working with seniors allow a conclusion that participation in the above-mentioned activities contributes to the building of social ties, enrichment of existing knowledge and acquisition of new skills. Participation reduces the risk of social exclusion and demonstrates the potential that seniors can use employ in education, culture or the labour market. Future educational initiatives for senior citizens should include and further develop activities related to support for new technologies, safety and intergenerational integration.